Lung donation after medical assistance in dying at home. Issue 1 (10th September 2020) - Healey, Andrew; Cypel, Marcelo; Pyle, Helen; Mills, Caitlin; Heffren, Jodie; Katz, David; Smith, Justin; Teranishi, Robert; Lavery, Susan; Beitel, Janice; MacLean, Janet; Prodger, Dwight; et al.
Abstract : Organ donation after medical assistance in dying (MAID) has only been possible for patients having the MAID procedure performed at a hospital facility due to prohibitive warm ischemic times. Herein, we describe a protocol for lung donation following MAID at home and demonstrate excellent postoperative outcomes. Lung donation following MAID at home is possible and should be considered by transplant programs. Abstract : This report describes the successful use of lungs from a donor who elected to undergo medically assisted death at home.